Cholinergic Urticaria Associated with Acquired Generalized Hypohidrosis: Two Case Reports and Review of the Literature - Cíntia Cruz; Filipa Alexandra Matos Tavares Semedo; Elza Maria Morgado Tomaz; Luís Miguel Nabais Borrego (Sociedade Portuguesa de Dermatologia e Venereologia, 2021)
Cholinergic urticaria is a relatively common condition defined by itching, redness and whealing induced by exercise and passive warming. In turn, acquired idiopathic generalized anhidrosis is a rare disorder of unknown pathogenesis, characterized by an impairment in total body sweating despite exposure to heat or exercise. We report two cases of this extremely rare association of cholinergic urticaria and acquired generalized hypohidrosis, and briefly review current knowledge with regard to classification, ethiopathogenesis and therapeutic options.